Corn Diversification through Training on Tuna Fish Bone Flour-Fortified Cookies in Pilolalenga Village, Gorontalo Regency - A. Dali, Faiza; Kaharu, Anton; Husain, Rahim; Apriliani , Silvana (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the knowledge and practical skills of members of the Karya Nyata Farmer Group, local housewives, and the Karang Taruna in local food diversification through the production of corn flour cookies fortified with tuna fish bone flour. The program introduced an innovative value-added food product utilizing locally available agricultural resources and fishery by-products while promoting local food diversification and the sustainable utilization of fishery waste. The activities were implemented through the Thematic Community Service Program (KKN Tematik I) of the State University of Gorontalo using a Participatory Action Research (PAR) approach. The implementation process included local potential identification, program planning, hands-on training, and program evaluation using pre-test and post-test assessments, participant response questionnaires, and organoleptic evaluation. Pre-test and post-test data were analyzed descriptively and presented as percentages. The participants' average knowledge score increased markedly from 41.8% in the pre-test to 85.8% in the post-test. Two cookie variants, chocolate and vanilla, were successfully produced and received favorable acceptance from the panelists. The chocolate variant achieved a higher overall acceptability score (4.36) than the vanilla variant (3.86). Overall, the program effectively improved participants' knowledge and practical skills in processing corn flour and tuna fish bone flour into acceptable value-added food products, thereby supporting local food diversification and promoting the sustainable utilization of fishery by-products.